Laboratory test of Beauveria bassiana (Balsamo-Crivelli) Vuillemin s.l. (Hypocreales: Clavicipitaceae) baits for the biocontrol of the Toad grasshopper pest, Bufonacris claraziana (Saussure) (Orthoptera: Tristiridae) - Mariottini, Yanina (2022)
Background: The Toad grasshopper pest, Bufonacris claraziana (Saussure) (Orthoptera: Tristiridae) is an endemic species of the Argentine Patagonia region. Among the Tristiridae family, it is the only species recognized as harmful to agricultural and livestock activities in the country. Outbreaks of B. claraziana have become a recurring phenomenon in the recent years, affecting different areas of the Patagonian provinces. The aim of this study was to evaluate, as laboratory bioassays, the mortality in young nymphs of this species treated with bait formulations of the entomopathogenic fungus Beauveria bassiana (Hypocreales: Clavicipitaceae). Results: The two treatments performed, one of them (I) with conidia of B. bassiana only and the other (II) with conidia of B. bassiana plus canola oil as phagostimulant, produced significantly higher mortality than the control (p < 0.05). At 10 days from the start of the bioassay, the mortality registered in the treatment II (53.33%) was higher than that in the treatment I (23.33%) (p < 0.05). This difference was similar at 15 days post-treatment, mortality reached in treatment II (93.33%) higher than in treatment I (73.33%). Conclusions: Results demonstrated that the combination of canola oil with wheat bran makes the bait with conidia of B. bassiana more attractive for nymphs of B. claraziana, enhancing mortality over a shorter interval of time.